The hornblende and biotite in an anomalous lodranite Yamato 983119. - Masahiro, Yasutake; Akira, Yamaguchi (2017)
第8回極域科学シンポジウム/個別セッション：[OA] 南極隕石 12月5日（火）国立極地研究所 1階交流アトリウム The Eighth Symposium on Polar Science/Ordinary sessions: [OA] Antarctic meteorites Tue. 5 Dec./Entrance Hall (1st floor), National Institute of Polar Research conference object